Negotiating The Meaning Of Early Marriage In Tiktok Audience Comments: A Critical Discourse Analysis - Jamiah, Ririn; Vanisya, Winda (KOMUNIKA, 2026)
The social and economic changes over the past several decades have significantly impactedthe perceptions of marriage among the younger generation, leading to a tendency to postponesuch commitments. However, a counter-narrative has emerged on social media platforms,especially TikTok, a counter-narrative has emerged presenting early marriage as a rationaland courageous choice. This study endeavors to analyze the ways in which the meaning of'marrying young' is negotiated by audiences in their responses to content on the TikTokaccount @Azkiavee. Employing a qualitative methodology, the research is qualitative,employing Norman Fairclough's three-dimensional Critical Discourse Analysis (CDA) toexamine comments on nine videos that present narratives supporting early marriage. Thefindings indicate that viewers actively produce counter-discourse centered on three primarythemes: firstly, emphasizing individualization of life choices as a form of resistance against thegeneralization of the creator's personal experience; secondly, rejecting the normalization ofearly marriage discourse prevalent on social media; and thirdly, framing education and careerpursuits as alternative rationalities for the younger generation. These results substantiate thenotion that TikTok comment sections serve as discursive arenas where the meaningsassociated with marriage are negotiated, with Indonesian young women actively contestinggender expectations embedded within creators' narratives.